Trimucytin: A Collagen-Like Aggregating Inducer Isolated from Trimeresurus mucrosquamatus Snake Venom - Teng, Che-Ming; Ko, Feng-Nien; Tsai, Inn-Ho; Hung, Man-Ling; Huang, Tur-Fu (Thrombosis and Haemostasis, 1993)
Trimucytin is a potent platelet aggregation inducer isolated from Trimeresurus mucrosquamatus snake venom. Similar to collagen, trimucytin has a run of (Gly-Pro-X) repeats at the N-terminal amino acids sequence. It induced platelet aggregation, ATP release and thromboxane formation in rabbit platelets in a concentration-dependent manner. The aggregation was not due to released ADP since it was not suppressed by creatine phosphate/creatine phosphokinase. It was not either due to thromboxane A2 formation because indomethacin and BW755C did not have any effect on the aggregation even thromboxane B2 formation was completely abolished by indomethacin. Platelet-activating factor (PAF) was not involved in the aggregation since a PAF antagonist, kadsurenone, did not affect. However, RGD-containing peptide triflavin inhibited the aggregation, but not the release of ATP, of platelets induced by trimucytin. Indomethacin, mepacrine, prostaglandin E1 and tetracaine inhibited the thromboxane B2 formation of platelets caused by collagen and trimucytin. Forskolin and sodium nitroprusside inhibited both platelet aggregation and ATP release, but not the shape change induced by trimucytin. In quin-2 loaded platelets, the rise of intracellular calcium concentration caused by trimucytin was decreased by 12-O-tetradecanoyl phorbol-13 acetate, imipramine, TMB-8 and indomethacin. In the absence of extracellular calcium, both collagen and trimucytin caused no thromboxane B2 formation, but still induced ATP release which was completely blocked by R 59022. Inositol phosphate formation in platelets was markedly enhanced by trimucytin and collagen. MAB1988, an antibody against platelet membrane glycoprotein Ia, inhibited trimucytinand collagen-induced platelet aggregation and ATP release. However, trimucytin did not replace the binding of 125I-labeled MAB1988 to platelets. Platelets pre-exposed to trimucytin were resistant to the second challenge with trimucytin itself or collagen. It is concluded that trimucytin may activate collagen receptors on platelet membrane, and cause aggregation and release mainly through phospholipase C-phosphoinositide pathway.